Carbon Nanotube Covalently Attached Laccase Biocathode for Biofuel Cell - Rizmahardian Ashari Kurniawan; Aulani Aulanni'am; Fa-Kuen Shieh; Peter Po-Jhen Chu (The Journal of Pure and Applied Chemistry Research, 2013)
Biocathode for biofuel cell was prepared by covalently immobilizedLaccaseon CNT (CNT-Laccase) using glutaraldehyde as conjugates. Successful laccase immobilization was confirmed by Fourier Transform Infrared (FTIR) Spectrophotometry, Surface Electron Microscopy (SEM) and Thermogravimetric Analysis (TGA). Immobilization affected Laccase enzymatic activity where it boosts the stability at high temperature and neutral pH. At temperature 65ºC, free Laccase completely loss its activity, while CNT-Laccase still retaining 57.12% of its activity at 45ºC. The activity of CNT-Laccase at pH 7 was 7.04% of activity at pH 5 which was higher than that of free Laccase. CNT-Laccase was able to perform oxygen electroreduction with addition ABTS (2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) as mediator. Performance of oxygen electroreduction activity was also determined by type and composition of binding polymer. Nafion was able to provide better environment for oxygen electroreduction activity compare to polyvinyl alcohol (PVA). Current density resulted in using Nafion in ratio 1:10 to buffer volume was 1.31 mA/cm2, which was higher than that of PVA (1.01 mA/cm2). Increasing binding polymer ratio into 1:2 and 1:1 undermined oxygen electroreduction activity.